Retrospective analysis of VES-13 questionnaires in the Senior Women's Breast Cancer Clinic at Sunnybrook Health Sciences, Toronto, Ontario, Canada. Issue 4 (May 2022) - Zereshkian, Arman; Khan, Benazir Mir; Cao, Xingshan; Henry-Noel, Nayanee; Menjak, Ines; Mehta, Rajin; Bristow, Bonnie; Trudeau, Maureen; Neve, Matthew; Norris, Mireille; Pasetka, Mark; Rice, Katie; et al.
Abstract: Purpose: Vulnerable Elder Survey (VES-13) is a screening tool used in assessing older vulnerable patients at risk of functional decline. We sought to evaluate how VES-13 tool would impact oncologist referral pattern to geriatricians as our primary outcome. We also sought to better understand how VES-13 scores impacted referral to additional services (allied healthcare), and modification to oncological treatment. Methods: A retrospective review of VES-13 questionnaires completed by older women (age 70 or older) with breast cancer referred to the Senior Women's Breast Cancer Clinic (SWBCC) was undertaken. Patients with a VES-13 score of three or greater, who were at significantly higher risk of functional decline, had further retrospective chart review for risk factors that would contribute to functional decline such as Eastern Cooperative Oncology Group (ECOG) score, social supports, and current living situation. The primary and secondary endpoints described above were analyzed through bivariate comparisons and multivariable logistical regression to determine if there was any statistical significance ( p < 0.05). Results: 701 patients completed VES-13 form, of which 235 (33.5%) had a VES-13 score of three or greater. Less than 5% of oncologists documented VES-13 scores in their notes, with less than 5% of patients being referred for geriatric services. Neither VES-13 ( p = 0.900) nor ECOG ( p = 0.424) were associated with referral for geriatrics assessment. Referral to allied healthcare services was significantly associated with (ECOG) score ( OR 2.24 [1.49–3.37], p < 0.0001), while not significantly associated with VES-13 score (OR 0.89 [0.78–1.02], p = 0.102). VES-13 (OR 1.23 [1.04–1.45], p = 0.014) and ECOG (OR 2.37 [1.29–4.37), p = 0.005) were both associated with modification in oncology treatment (chemotherapy or radiation). Conclusion: Approximately one third of our population was at risk of functional decline. VES-13 scores were infrequently mentioned in oncologists notes from their clinical assessments, with very few patients being referred for geriatric assessment. By not collecting and analyzing VES-13 scores, and relying on performance status alone, there is a missed opportunity in assessing for functional decline and reducing potential complications from treatment for our patients.